Pengaruh GRC Disclosure dan ROA Terhadap Return Saham Sektor Asuransi di BEI Tahun 2022 -2024 - Kadek Ariati; Ni Komang Sumadi; Ni Wayan Alit Erlina Wati (UNHI Press, 2026)
Stock returns denote the economic benefits accrued by investors from holding ownership stakes in a firm. An escalation in stock returns is commonly interpreted as a signal of robust corporate performance, which in turn tends to stimulate investor appetite. The drivers of stock returns are inherently multidimensional, encompassing both financial and non-financial attributes. This study is designed to scrutinize the interrelationship between Governance, Risk, and Compliance (GRC), Return on Assets (ROA), and stock returns. The empirical scope of this research encompasses a cohort of 18 insurance firms registered onthe IDX throughout the 2022–2024 observational span. A census (saturated sampling) technique was implemented, whereby the entire population was incorporated as the analytical sample. Data were derived from corporate annual reports employing a documentation-based collection method. The analytical approach utilizes multiple linear regression, facilitated through SPSS software. The procedure was initiated with descriptive statistical analysis to delineate data characteristics, followed by classical assumption diagnostics, including tests of normality, multicollinearity, autocorrelation, and heteroscedasticity. Model robustness was subsequently appraised using the coefficient of determination (R²) alongside the F-test, while hypothesis testing was conducted via the t-test. The empirical findings substantiate that GRC disclosure encompassing governance, risk, and compliance dimensions exerts a positive and statistically signnificant effect on stock returns. Conversely, although ROA demonstrates a positive directional association with stock returns, its influence does not attain statistical significance within the context of the insurance sector.